Some aspects of using modern innovative nanotechnologies in dentistry technical solutions, dilemma of implantation - Chertov, S. O.; Kaminskyy, V.; Tatarina, O.; Mandych, O.; Oliinyk, A.; Чертов, Сергій Олександрович (My University, 2023)
In the article, the authors analyze the problem of using modern innovative nanotechnologies in dentistry. Currently, nanotechnology is used in treatment, prosthetics, preventive care of the oral cavity and teeth. Based on this, the use of nanotechnology in dentistry has a number of advantages compared to the traditional materials used, as they are more effective, affordable, structured, meet all modern parameters, and have high quality. Despite the widespread use of nanotechnology, in some cases, they may carry certain risks. Nanomaterials have higher activity, high permeability through the skin, lungs, and digestive tract. But the impact of nanoparticles on the body remains unexplored. In addition to safety problems of nanomaterials, their production is associated with a number of other problems: engineering, biological, and social. Specialists think about new ways to solve current professional problems. Time will tell how successful the process of integrating narrow-profile research into practical activity will be. The development of new and implementation of existing nanotechnology medical technologies is a promising direction of the development of modern dentistry.
Keywords: nanotechnology; nanomaterials; nanoparticles; dentistry; medicine